Prognostic significance of molecular subgroups in survival outcome for children with medulloblastoma in Malaysia - Rajagopal, Revathi; Teng, Ay Jiuan; Jawin, Vida; Wong, Oy Leng; Mahsin, Hakimah; Abd Rani, Nor Haizura; Yap, Tsiao Yi; Gunasagaran, Kogilavani; Thevarajah, Asohan; Yeoh, Seoh Leng; Ong, Gek Bee; Ariffin, Hany; et al. (Frontiers in Oncology, 2023)
We thank the reviewers and editors for the valuable feedback, which has certainly improved the quality of our manuscript. Please see point-by-point responses below. We have highlighted the changes in blue in the manuscript.It is a great pleasure to review the manuscript entitled ¨Prognostic significance of molecular subgroups in survival outcome for children with medulloblastoma in Malaysia¨. This is a great paper with clinical outcome and molecular-histopathological correlation. 1.I would comment in the conclusion-discussion a little more how to improve and reduce dropout from treatment. On the other hand, I would comment on death before and during treatment, how to reduce this numbers. I would compare treatment abandonment and death/complication with high income countries and other LMIC as well. The numbers of treatment related complications (such as sepsis and post-surgical mortality) are very worrying and require further analysis. In the conclusion, it would also include the delay of radiotherapy as another point to work on as the main barrier to achieving better outcome (together with abandonment of treatment and death during treatment).We thank the reviewer for this suggestion. We have added the following statements in the results, discussion, and conclusion sections.Overall, eight families refused treatment and the abandonment rate for the whole cohort was 19.5%.